2021
DOI: 10.18231/j.ijceo.2021.062
|View full text |Cite
|
Sign up to set email alerts
|

Eyestrain and associated problems among undergraduate medical students undergoing e-learning/teaching methods during Covid-19 pandemic

Abstract: Increase in usage of digital devices and mandatory e-learning imposed during the Covid 19 pandemic curfew may have given rise to an emerging public health threat of digital eyestrain among undergraduate medical students in the state. The study aimed to assess the distribution of digital eyestrain among undergraduate medical students and to determine the association between digital eyestrain and screen time spent on different digital devices for e-learning and social media use.A cross sectional, questionnaire b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, during and post-Covid times, multiple studies have reported varied prevalence of dry eye among medical students all over the world. [ 7 - 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during and post-Covid times, multiple studies have reported varied prevalence of dry eye among medical students all over the world. [ 7 - 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 - 6 ] However, during the covid pandemic, researchers expected more screen time among medical students as well; thus, many dry eye studies were conducted among medical students with varied results on the prevalence of DED. [ 7 - 10 ]…”
mentioning
confidence: 99%
“…Since the COVID epidemic started in China at the end of December 2019, then it has rapidly spread globally. Hundreds of millions of people have been infected with about 350 million and millions of people have died about 5.6 million people (WHO), Vietnam is a neighboring country, next to China where the deadly virus originated, it is the rapid spread of the virus when there is contact between people or the environment contains many viruses that lead to the mandatory block down (social distancing) is the Vietnamese government's response to the COVID 19 pandemic, to prevent a large-scale outbreak, Vietnam has repeatedly locked down on a nationwide level to prevent epidemics, with the policy Vietnam has initially succeeded in preventing the initial 3 attacks of COVID 19, however, the 4 th wave caused an outbreak in Vietnam about 1.8 million people infected and about 32,000 died (Wikipedia), It is not only harmful to health but also seriously affects many areas of social life, public and crowded activities such as sports (Bruno &, Dalton & Edson 2020) or education (1,37). Billions of students at home as COVID 19 school closures expend UNESCO) are affected, in today's modern context, when concentrated learning in the lecture hall contains many dangerous risks that can cause disease outbreaks on a large scale, there is still only one way.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, an e-learning system is like a learning environment including data storage and transmission technologies. As a result, learners can interact with each other right on the online training system without having to meet face-to-face, learners can actively study anytime, anywhere, send feedback and receive feedback immediately from teachers…the cost of delivering instruction and the speed with multi-media permit the achievement of preset learning (Richad E Clark et al, 1992) [24] When applying this method, many difficulties have arisen for teachers and learners, which are difficulties in using new technology, some students can't afford modern computer technologies and lack focus on the lesson (R Raja, P C Nagasubramami 2018) [10] , Physical health problems such as eye strain, neck and shoulder fatigue, headaches when using computers and phones for a long time (Aqueen Joju 2021) [1] , mental health studies (Elmer T, Mepham K, Stadtfeld C 2020) [6] have shown that neurological diseases such as stress, anxiety, depression, and mental consequences are higher in women than in men. The main purpose of learning physical education include improving health and function of the body for learners, Forming healthy habits, providing knowledge about sports training and injury prevention, releasing stress, change the learning environment for learners, Physical education has a good effect on improving the learning quality of other subjects, enhance social relationships between individuals, groups of individuals, the ability to coordinate in the game and apply knowledge learned in competition practice, through sporting events (Richard Bailey et al, 2009) [11] , However, in the context of limited contact and mass gatherings during the period of social distancing, many contents cannot be implemented, and especially physical education, learning needs a yard as well as an environment for people to study.…”
Section: Introductionmentioning
confidence: 99%